Financial Policies and the Prevention of Financial Crises in Emerging Market Economies - Mishkin, Frederic S. (World Bank, Washington, DC, 2014)
The author defines a financial crisis as a disruption in financial markets in which adverse selection and moral hazard problems become much worse, so that financial markets are unable to efficiently channel funds to those who have the most productive investment opportunities. As financial markets become unable to function efficiently, economic activity sharply contracts. Factors that promote financial crises include, mainly, a deterioration in financial sector balance sheets, increases in interest rates and in uncertainty, and deterioration in nonfinancial balance sheets because of changes in asset prices. Financial policies in 12 areas could help make financial crises less likely in emerging market economies, says the author. He discusses: Prudential supervision. Accounting and disclosure requirements. Legal and judicial systems. Market-based discipline. Entry of foreign banks. Capital controls. Reduction of the role of state-owned financial institutions. Restrictions on foreign-dominated debt. The elimination of too-big-to-fail practices in the corporate sector. The proper sequencing of financial liberalization. Monetary policy and price stability. Exchange rate regimes and foreign exchange reserves. If the political will to adopt sound policies in these areas grows in emerging market economies, their financial systems should become healthier, with substantial gains both from greater economic growth and smaller economic fluctuations.